Influences Of Learning Environment And Basic Psychological Needs On Self-determined Learning Of Postgraduate Students: The Mediating Effects Of Heutagogical Activities - Tiew, Chia Chun (2024)
This study aims to investigate the influence of the learning environment and basic psychological needs on self-determined learning among postgraduate students. The mediating effect of heutagogical activities on the relationship between these two variables was also examined. A mixed-methods study was conducted at a research university in Malaysia to achieve the research objectives. A total of 664 postgraduate students were sampled through an online questionnaire. Four highly valid and reliable instruments were used to collect data namely Postgraduate Self-Determined Learning Questionnaire, Learning Environment Scale, Basic Psychological Needs Satisfaction Scale, and Heutagogical Activities Scale. Next, qualitative data were obtained through semi-structured interviews with 28 postgraduate students. Descriptive analysis results showed that postgraduate students had a high level of self-determined learning (M=3.18; SD=0.41). The involvement of students from medical, dental, and health, engineering, and arts programs in explore heutagogical activities was high, while their participation in learning activities requiring connection with others and information sharing were low. The structural equation modeling (SEM) results indicated that the learning environment (β=0.150, p< 0.01) and basic psychological needs (β=0.379, p< 0.01) had a direct effect on self-determined learning. Furthermore, heutagogical activities had a significant mediating effect on the relationship between these two variables.